2016
DOI: 10.1177/1077546316632932
|View full text |Cite
|
Sign up to set email alerts
|

An effective vibration reduction concept for automotive applications based on granular-filled cavities

Abstract: The acoustic behavior of a combustion engine is primarily dominated by the sound radiation of the oil pan. Therefore, the vibration behavior of the oil pan as the prominent noise emission source is investigated in this paper. The aim of this study is to present a new vibration reduction concept, which is based on the property of high damping possessed by granular materials. The efficiency of this concept is proven by measurements via a scanning laser vibrometer. Finally, it is shown that it is possible to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Regarding the properties of particle damping, the literature states a number of qualitative findings. First, the damping behaviour of granular materials is highly nonlinear due to impacts and sliding between the particles (Duvigneau et al 2016;Fowler et al 2001, p. 1). In most publications, the nonlinearity is indicated as being dependent on the excitation amplitude.…”
Section: Particle Dampingmentioning
confidence: 99%
“…Regarding the properties of particle damping, the literature states a number of qualitative findings. First, the damping behaviour of granular materials is highly nonlinear due to impacts and sliding between the particles (Duvigneau et al 2016;Fowler et al 2001, p. 1). In most publications, the nonlinearity is indicated as being dependent on the excitation amplitude.…”
Section: Particle Dampingmentioning
confidence: 99%
“…The modeling of the encapsulation materials is not discussed here in detail, see [3]. Detailed numerical analyses have been conducted without and with different types of thermo-acoustic engine encapsulations; some results are presented in [3,4]. The results have also been experimentally evaluated with acoustic measurements in an engine test bench as seen in Fig.…”
Section: Pcyl(ω)mentioning
confidence: 99%
“…Also, they showed the high damping capability of lead compared to other metallic materials. Fabian et al showed particle impact damper's applications in automobile applications [11].…”
Section: Introductionmentioning
confidence: 99%